Respuestas

2016-04-29T00:55:01+02:00
V₀ = ṽ₂ − ½ a t₂ = ṽ₁ − ½ a t₁ 
10 m/s − ½ a m/s² × 50 s = 12,5 m/s − ½ a m/s² × 20 s. 
(10 − 25 a) m/s = (12,5 − 10 a ) m/s. 

• Agrupando términos, 

10 a − 25 a = 12,5 − 10 
−15 s · a = 2,5 m/s 
a = − 2,5 / 15 = −5 / 30 = −1/6 m/s² 

• Lo que resta es simple. Puesto que v₀ = ṽ₂ − ½ a t₂, entonces resulta que v₀ = 10 m/s − (−1/12 m/s² × 50 s = 14,16666... m/s. Ahora, recordando que v² − v₀² = 2 a s —donde v = 0, despejando s, tenemos que 

► s = −v₀² / 2 a = −14,1666...² m²/s² / (2 × 1/6) m/s² = 602,08 m.